Determinants Of Pulmonary Vital Capacity Female Confectionery Workers - Cahyono, Tri (Buletin Keslingmas, 2025)
Background, small industries are mostly low surveillance, have potential occupational risks to the vital capacity of the lungs derived from the characteristics of the worker and the quality of the environment. A preliminary survey on confectionery found young workers, low education, no personal protective equipment and poor environmental sanitation. The purpose of the study was to determine the determinant factors of the lung capacity of women garment confectioners. Methods, types of observational research, analytics. Independent variables of worker characteristics and air quality, dependent variables of lung vital capacity. The sample population of 18 women confectioners, methods of data collection interviews, observation and measurement. Simple and multiple regression correlation analysis. Results,  average pulmonary vital capacity was 1,449.56 ml,  age 30.78 years (r = 0.346), education 72.2% elementary school (r = 0.217), BMI 24.41 (r = 0.044), history of Ispa disease 88.9% never (r = -0.269), mask use 88.9% not used (r = -0.134), working period (2.56 years (r = -0.221), working time 10.50 hours (r = 0.018), occupational history of 50% dusty (r = -0.188), average temperature 33.170C (r = 0.378), average humidity 44.97% (r = -0.389), indoor dust 0.09 mg/m3 (r = -0.391),  home dust 0.03 mg/m3 (r = -0.436). All independent variables of bivariate correlation analysis were insignificant. Multivariate analysis of double regression correlation r = 0.875, p = 0.002, Y = (-671.14) + 27.29Xage + 401.18Xeducation + (-198.30)Xworking time + (-265.22)Xwork history + 49.49Xtemperature. Conclusions, determinants of lung capacity; age, education, working age, employment history and temperature. It is necessary to install an exhauster for the vacuum cleaner and the air temperature outside the room.